Calix[n]triazolium based turn-on fluorescent sensing ensemble for selective adenosine monophosphate (AMP) detection. Issue 91 (1st November 2021) - Cho, Jihee; Shin, Jinwoo; Kang, Minjung; Verwilst, Peter; Lim, Changhyun; Yoo, Hanbin; Kim, Jeung Gon; Zhang, Xingcai; Hong, Chang Seop; Kim, Jong Seung; Kim, Sanghee
Abstract : We report a series of calix[ n ]triazoliums showing excellent selectivity for AMP. The unique supramolecular ensemble exhibits a selective turn-on fluorescence response towards AMP over various anions, including adenosine polyphosphates. Abstract : A novel calix[ n ]triazolium was synthesized and exhibited excellent selectivity for AMP. The binding between calix[ n ]triazolium and chromenolate anions forms a non-fluorescent complex and the resulting supramolecular ensemble selectively detects AMP in water and induces "turn-on" fluorescence. The sensing platform is the first macrocyclic system to discriminate AMP from ADP and ATP through fluorescence changes.